THE SUSPICION OF THE POSSIBILITY FOR A DIALOGUE OF CONSCIOUSNESSES IN DOSTOEVSKY - Максим Вак (Докса, 2016)
The article is devoted to researches of dialogue of consciousnesses in Dostoevsky’ philosophy and literature creativity. The ideas of M. Bakhtin and E. Levinas are methodological basis of the investigation. Bakhtin presents the novelty of Dostoevsky’s writing almost as a paradox of a divine creation – Dostoevsky creates his heroes in such a way that they are free from their creator, and Dostoevsky does not have the last, determined word concerning their destiny. They keep their secrets from him as though he did not create them. This situation, if Bakhtin is right, gives rise to disturbing questions concerning how to read these novels. We have analyzed a lot of the most significant moments in the novels we can say the same concerning all the examples that Bakhtin presents in order to demonstrate the dialogical structure of Dostoevsky’s writings. For our opinion Bakhtin’s analysis of style and structure is fine and perceptive but he does not pay attention to the fact that the main problem is not in the presence of this structure but in the question of the possibility of its presence. Sooner, the dialogical structure is present in Dostoevsky’s writings despite the impossibility of dialogue. One hears the other despite the impossibility to hear the other. One of the central problems is how it is possible to hear the other if one hears only oneself; how it is possible to address the other if there is only my ego, my consciousness that always hears out of itself and assimilates the other. It is not the dialogue, but the impossible possibility of dialogue that creates the climate of Dostoevsky’s novels. To demonstrate this we have followed Bakhtin in his analyses of Dostoevsky’s discourse.